6(6+7x)=456

Simple and best practice solution for 6(6+7x)=456 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(6+7x)=456 equation:


Simplifying
6(6 + 7x) = 456
(6 * 6 + 7x * 6) = 456
(36 + 42x) = 456

Solving
36 + 42x = 456

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-36' to each side of the equation.
36 + -36 + 42x = 456 + -36

Combine like terms: 36 + -36 = 0
0 + 42x = 456 + -36
42x = 456 + -36

Combine like terms: 456 + -36 = 420
42x = 420

Divide each side by '42'.
x = 10

Simplifying
x = 10

See similar equations:

| 4(-18-2)-5*18=1 | | -2x-1/2=x/5 | | (2x+3)+(x-6)=90 | | 2+2-4+3-7+8= | | -6n+15=-5n-1 | | 2(4-5x)+9=2x-23-8x | | 7(6x+7)=91 | | 5+6x=3+5x-8 | | 3x=2x-17.5 | | 2x/5-2x-1/2=x/5 | | 5*6+5x+6x=30x | | 7(8+x)=98 | | 4(x+3)+28=-4x | | -3x-8=5y+32 | | 6x=4y+8 | | (5x-2)(2x+7)= | | 4(y+3)=3y+13 | | 8(7-x)=4(3x-16) | | 8y-6=6y+6 | | 6(3+2x)=54 | | x^2-13x+15=-3x-1 | | 7x+2=12+x | | -16x-20=-13x+55 | | (a+b+c)*(a+b-c)= | | 7x^2+28x-315=0 | | 10=42-2x | | 7x+21=4+2x | | 6(7+2x)=114 | | 2x-3+5x-8=6x+54 | | x^2+4x+10=7 | | x^2+2x=1000 | | 5a-6=3a-8 |

Equations solver categories